COMPARATIVE ASSESSMENT OF BULL SPERM MOTILITY AND CONCENTRATION: CONVENTIONAL METHODS VERSUS PORTABLE ANDROSCOPE CASA SYSTEM - Arifiantini, Raden Iis; Gusman, Khalis Talitha; Agil, Muhammad; Karja, Ni Wayan Kurniani (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Operational implementation, such as laboratory staff and equipment, differ for each frozen semen producer, resulting in variability in the quality assessment of the frozen semen produced. Conventional assessments subject to subjectivity, human error, and high variability. Computer-assisted semen analysis (CASA) is considered more objective. This study aimed was to conduct a comparative analysis of motility and concentration assessment of frozen semen sperm using conventional and the portable CASA AndroScope. Twenty-one laboratory assistants from 21 national and regional frozen semen producers participated in this study. Sperm motility and concentration were assessed conventionally (using a Neubauer chamber) and AndroScope was used with five replicates. The results of the comparison of sperm motility scores revealed significant differences (p<0.05) between conventional examination and using AndroScope. The results of the comparison of the sperm concentration calculations revealed no significant difference (p>0.05) between the calculations performed using the Neubauer chamber and AndroScope. Assessment with the AndroScope is considered reliable and can replace conventional assessment in assessing motility and sperm concentration, thereby improving and standardizing the assessment performed by frozen semen producers.